Uso do Portal de Periódicos da CAPES pelos alunos do Programa de Pós-graduação em Produtos Naturais e Sintéticos Bioativos - Duarte, Janete Silva (2010)
This quantitative research aimed to analyze the use of CAPES Periodic Portal by the students of the Post-graduation Program in Bioactive Synthetic and Natural Products from UFPB. It presents concepts related to information users and the use of information. Moreover, it uses the Technology Acceptable Model (TAM) as data collection tool, by means of a questionnaire. Furthermore, the research is characterized as an exploratory and descriptive one, under an alternative approach. The sample is formed by 88 Master and Doctor in Science students of the Post-graduation Program in Pharmacy, which are described as a young population. Also, most of them are women and never participate of training about the CAPES Periodic Portal. The results revealed some problems about the website use like difficulties in the website use; insufficient number of computers in the research laboratories; and difficulties in access the website outside the university environment. On the other hand, the research showed positive aspects as: a strong intention in using the Portal, even after the students have concluded their postgraduation courses; time compatibility of the researcher with the research laboratory. Another positive aspect the students are motivated by their professors and by their own colleagues to use the Portal. Then, it can be concluded that the utility perceived is not influenced by the facility in use. Therefore, it presents a strong intention in the use of the CAPES Periodic Portal.